2014
DOI: 10.5120/18115-9346
|View full text |Cite
|
Sign up to set email alerts
|

Cyber-Attack Classification using Improved Ensemble Technique based on Support Vector Machine and Neural Network

Abstract: Cyber-attack classification and detection process is based on the fact that intrusive activities are different from normal system activities .Its detection is a very complex process in network security. In current network security scenario various types of cyber-attack family exist, some are known family and some are unknown one . The detection of known attack is not very difficult it generally uses either signature base approach or rule based approach, but to find out the unknown one is a challenging task. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Govindarajan and Chandrashekaran [6] which also put forth an anomaly intrusion detection system to assess the efficiency of the RBF-SVM hybrid system by carrying out various experiments on the NSL-KDD dataset. The authors in [7] suggested an improved ensemble classifier or a cascaded SVM classifier employing more than one kernel function, which is Gaussian in nature. The harnessing of graph-based neural network techniques eases the process of features' collection of different cyber-attack data.…”
Section: Related Workmentioning
confidence: 99%
“…Govindarajan and Chandrashekaran [6] which also put forth an anomaly intrusion detection system to assess the efficiency of the RBF-SVM hybrid system by carrying out various experiments on the NSL-KDD dataset. The authors in [7] suggested an improved ensemble classifier or a cascaded SVM classifier employing more than one kernel function, which is Gaussian in nature. The harnessing of graph-based neural network techniques eases the process of features' collection of different cyber-attack data.…”
Section: Related Workmentioning
confidence: 99%
“…It total number is important to observe the total number of faults to assess the classifiers works [36]. The evaluation parameters represented on the following [37]: 1) Accuracy is the quality measurement for classifier, which can be calculated through mathematically finding the ratio of correct classified attempts number according to the total number of all classification attempts.…”
Section: Evaluation Parametermentioning
confidence: 99%